Edukasi juru pemantau jentik dalam pengendalian vektor demam berdarah dengue (DBD) di Desa Sukadadi Kecamatan Gedong Tataan - Sintia, Monica Bela Dwi; Triyoso, Triyoso; Kusumaningsih, Dewi (JOURNAL of Public Health Concerns, 2025)
Background: The incidence of dengue fever in Indonesia remains relatively high, with 88,593 cases and 612 deaths spread across 456 regencies/cities in 34 provinces. According to the Pesawaran Regency Health Office profile, the highest number of dengue fever cases in 2023 was in Gedong Tataan District, with 51 cases. This disease is classified as an infectious disease and, if left uncontrolled, has the potential to become an Extraordinary Event (KLB) and cause an epidemic. One effort that must be taken is to optimize the knowledge of mosquito larvae monitors (Jumantik) and the most appropriate method to prevent dengue fever through vector control. Purpose: To improve the knowledge of mosquito larvae monitors (Jumantik) in controlling dengue hemorrhagic fever (DHF) vectors. Method : The activity was conducted in July 2025 in Sukadadi Village, Gedong Tataan District, Pesawaran Regency. The population for this activity was all mosquito larvae monitor (jumantik) cadres in Sukadadi Village, Gedong Tataan District. Using a purposive sampling technique, 10 mosquito larvae monitor (jumantik) cadres were selected as respondents. The activity consisted of counseling with presentations related to knowledge and vector control of Dengue Hemorrhagic Fever (DHF). Data processing used a one-group pretest-posttest approach to measure knowledge levels and changes in knowledge levels. Data were analyzed univariately to describe respondent characteristics, and bivariately using the Wilcoxon Signed Rank Test to determine differences in knowledge levels before and after the intervention. Results: The mean level of knowledge of respondents before the education program was 4.4 points with a standard deviation of 1.07 points. Meanwhile, the mean level of knowledge of respondents after the education program was 8.5 points with a standard deviation of 0.17 points. Conclusion: This health education activity, using leaflets, significantly improved the knowledge of mosquito larvae monitors (Jumantik) regarding Dengue Hemorrhagic Fever (DHF) vector control. This increase in knowledge demonstrates that the use of simple, easy-to-understand educational media is highly effective in conveying health information to mosquito larvae monitors (Jumantik) regarding the role and control of dengue vectors. Suggestion: It is recommended that simple yet effective health promotion media, such as leaflets, be used more actively in educational activities for mosquito larvae monitors (Jumantik) and the public. This media has been proven to increase understanding regarding dengue vector prevention and control. Keywords: Dengue Hemorrhagic Fever; Jumantik; Knowledge; Optimization Pendahuluan : Angka kejadian penyakit DBD di wilayah Indonesia masih tergolong tinggi dengan jumlah kasus sebanyak 88.593 dengan 612 kasus kematian yang tersebar di 456 kabupaten/kota dari 34 provinsi. Berdasarkan profil dinas kesehatan Kabupaten Pesawaran, pada tahun 2023 jumlah kasus demam berdarah tertinggi terdapat di Kecamatan Gedong Tataan dengan jumlah kasus sebesar 51 kasus. Penyakit ini masuk kategori penyakit menular yang apabila tidak dikendalikan akan dapat berpotensi menjadi Kejadian Luar Biasa (KLB) serta menimbulkan wabah. Salah satu upaya yang harus dilakukan ialah mengoptimalkan peningkatan pengetahuan Juru Pemantau Jentik (Jumantik) dan cara yang paling tepat untuk mencegah terjangkitnya penyakit DBD dengan pengendalian vektor penularannya. Tujuan: Untuk meningkatkan pengetahuan kader juru pemantau jentik (Jumantik) dalam pengendalian vektor Demam Berdarah Dengue (DBD). Metode: Kegiatan dilaksanakan pada bulan Juli 2025 di Desa Sukadadi, Kecamatan Gedong Tataan, Kabupaten Pesawaran. Populasi dalam kegiatan ini adalah seluruh kader jumantik di Desa Sukadadi,Kecamatan Gedong Tataan dan dengan menggunakan teknik purposive sampling mendapatkan 10 orang kader juru pemantau jentik (jumantik) untuk menjadi responden. Kegiatan dilakukan berupa penyuluhan dengan pemaparan materi terkait pengetahuan dan pengendalian vektor Demam Berdarah Dengue (DBD).  Pengolahan data dengan pendekatan one group pretest-posttest untuk mengukur tingkat pengetahuan dan perubahan tingkat pengetahuannya. Data dianalisis secara univariat untuk mendeskripsikan karakteristik responden, dan secara bivariat menggunakan Wilcoxon Signed Rank Test untuk mengetahui perbedaan tingkat pengetahuan sebelum dan sesudah intervensi. Hasil: Menunjukkan bahwa tingkat pengetahuan responden sebelum pemberian edukasi mendapatkan nilai mean 4.4 poin dengan nilai standar deviasi 1.07 poin. Sedangkan tingkat pengetahuan responden setelah pemberian edukasi mendapatkan nilai mean 8.5 poin dengan nilai standar deviasi 0.17 poin. Simpulan: Kegiatan ini merupakan pendidikan kesehatan melalui media leaflet secara signifikan mampu meningkatkan pengetahuan juru pemantau jentik (Jumantik) dalam pengendalian vektor Demam Berdarah Dengue (DBD). Peningkatan pengetahuan ini menunjukkan bahwa penggunaan media edukatif sederhana dan mudah dipahami sangat efektif dalam menyampaikan informasi kesehatan kepada kader jumantik terkait peranan dan pengendalian vektor DBD. Saran: Diharapkan untuk lebih aktif menggunakan media promosi kesehatan sederhana namun efektif, seperti leaflet, dalam kegiatan edukasi kader jumantik dan masyarakat. Media ini terbukti mampu meningkatkan pemahaman terkait pencegahan dan pengendalian vektor DBD